THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING (CTL) ON STUDENTS’ DESCRIPTIVE WRITING ACHIEVEMENT OF THE 2016/2017 TENTH YEAR STUDENTS OF SMK SWASTA MELATI - Eni Susanti; Ayu Indari (STKIP Budidaya Binjai, 2022)
The research aims to find out the effect of Contextual Teaching and Learning (CTL) on students’ descriptive writing achievement of the 2016/2017 tenth year students of SMK Swasta Melati. The problems that had been identified by the researchers are including that students were not interested in learning English especially in writing. This research uses descriptive writing in written test. The research deals with an experimental research design which seeks for the effect of Contextual Teaching and Learning (CTL) strategy on the students’ writing descriptive text achievement. The populations of this research were students of the tenth grade students of SMK Swasta Melati. The sample of the research consisted of 40 students. The study was an experiment and control research, the experiment class is X-1 and the control class X-2. The writing test was used to obtain the data on the variable. The final data then was analyzed by using technique of t-test analysis. The result shows that coefficient of tcounted (3.41) was greater than the ttable coefficient (1.68595). This means that there is any effect of Contextual Teaching and Learning (CTL) on the students’ achievement in writing a descriptive text of the 2016/2017 tenth year students of SMK Swasta Melati. Therefore, the hypothesis of the study is accepted.